2008
DOI: 10.1103/physrevlett.101.163001
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a Rydberg Series inH+H: A Heavy Bohr Atom

Abstract: We report on the realization of a heavy "Bohr atom," through the spectroscopic observation of a Rydberg series of bound quantum states at principal quantum numbers n=140 to 230. The system is made heavy by replacing an electron inside a hydrogen atom by a composite H- particle, thus forming a H+H- Coulombically bound system obeying the physical laws of a generalized atom with appropriate mass scaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 23 publications
1
43
0
Order By: Relevance
“…These studies found the spectra dominated by relatively short-range electronic molecular states. It was only recently that Vieitez et al observed spectral features corresponding to bound ion-pair states by using a laser-based xuv light source in a two-photon excitation scheme [19,20]. Consistent with the earlier investigations, the ion-pair resonances were observed in the photoexcitation yield of H coupling with short-range electronic molecular states.…”
supporting
confidence: 72%
“…These studies found the spectra dominated by relatively short-range electronic molecular states. It was only recently that Vieitez et al observed spectral features corresponding to bound ion-pair states by using a laser-based xuv light source in a two-photon excitation scheme [19,20]. Consistent with the earlier investigations, the ion-pair resonances were observed in the photoexcitation yield of H coupling with short-range electronic molecular states.…”
supporting
confidence: 72%
“…Selection rules impose that only Rydberg states converging to V + ) 6, N + ) 1 and 3 should be observable, which is indeed the case. Again, qualitatively some features of series interaction are visible in the spectrum of Figure 3 in ref 23. In the Rydberg series converging to V + ) 6, N + ) 3 the Fano q-parameter is found to vary as a function of the principal quantum number, indicative of an interaction between multiple channels.…”
Section: Experiments and Observationsmentioning
confidence: 76%
“…The states that undergo polar dissociation, though repulsive in the Franck-Condon region, will have minima at large internuclear separations, due to the 1=r potential between the fragments. These states have been shown to behave like a heavy Bohr atom with H À ion being orbited by a proton with large principal quantum numbers [27,28]. Several states that undergo vibrational autoionization and polar dissociation by photoabsorption in the range of 17.37-17.62 eV have been identified in H 2 , HD, and D 2 [29].…”
Section: Fig 2 (Color Online)mentioning
confidence: 99%